A COMPLEXIDADE ESPACIAL DA EXPLORAÇÃO SEXUAL COMERCIAL INFANTO-JUVENIL FEMININA: ENTRE TÁTICAS E ESTRATÉGIAS DE (IN) VISIBILIDADE - Nabozny, Almir (2007)
This research constructs elements for comprehension of social-spacial process of comercial infantile-juvenile feminine sex exploitation in Ponta Grossa, State of Paraná, Brazil. In the middle of a legal mark (regulator of distinctions between adults, children, adolescents) there are quotidian practises of the girls forming meanings around of sexuality, body and identities. The geographical space exercise an mediator role, composing relations and representations by the quotidianity. The focal group of this investigation is constituted by chidren and adolescents of female sex who are sexual exploited in a commercial way. The execution of this research is based on (a) sistematical observation of adult prostitution points; (b) analisis of proceedings of Infancy and Youth Judgeship of Ponta Grossa, Brazil; (c) reading of registers of occurrences of Conselho Tutelar Oeste (West Tutelary Council), after the year of 1990; (d) interviews with adults sex professionals; (e) interviews with professionals who works in institutions whose target public are adolescents and children; (f) dialogues with public security professionals; (g) interlocution with communitaries agents of Programa Saúde da Família (Family Health Program) and (h) investigation with the institutionalized children and adolescents that are in shelters, by half-structured interviews and corporal and visual expression. These various fronts are complementaries in the comprehension of the phenomenon enquired and they reforce the methodological validation. The research evidenced that the spatiality of the feminine infantile-juvenile sexual exploitation phenomenon is characterized by a high complexity and it does not presents a homogeneous standard. On the contrary, its survival is possible by the multiple spatial configurations. In this way, make feasible the practises fo the components agents in the spatial interdependence. These are invisible tactics to strategies referred to the State.